Trophic ecology of Acestrorhynchus falcirostris Cuvier, 1819 in island lakes on the lower stretch of the Solimões River, Amazon Basin - Lubich,C. (2024)
Abstract The aim objective of this study was to determine the trophic ecology of juvenile and adult Acestrorhynchus falcirostris during the rising and flood (high-water) period in six island lakes adjacent to the Solimões River. As such, we investigated: i) the trophic position, through the fractional trophic niche; ii) the niche breadth; iii) niche overlap and iv) the food strategy of the species. The specimens were collected during the years 2014 to 2017, using gillnets with mesh sizes ranging from 30 to 120mm between opposite knots. Through the analysis of stomach contents, the preference in the consumption of items of animal origin was observed. Juveniles consumed insects in greater proportions (IAi% = 50%), while adults consumed fish (IAi%=99,98%). Despite the large supply of food items available in the high-water period, juveniles were the only ones to consume items of allochthonous origin, such as insects. Juveniles presented a different dietary strategy and dietary composition to adults. Juveniles were omnivores with a generalist strategy, while adults were piscivores with a specialist strategy. Thus, the food composition, niche breadth, trophic position and feeding strategy of Acestrorhynchus falcirostris change due to the stage of development.